2011
DOI: 10.1002/cphc.201100595
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Nuclear Resonant Vibrational Spectra of Rubredoxin Using a Combined Quantum Mechanics and Molecular Mechanics Approach

Abstract: Nuclear resonant vibrational spectra of the reduced and oxidized form of a mutant of rubredoxin from Pyrococcus abyssii were measured and are compared with simulated spectra that were calculated by a combined quantum mechanics (QM) and molecular mechanics (MM) method. Density functional theory was used for the QM level. Calculations were performed for different models of rubredoxin. Realistic spectra were simulated with reduced models that include at least the iron center, the four cysteins coordinating it, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…In this context, quantum mechanics/molecular mechanics (QM/MM) calculations provide reliable structural information on a local region of biomolecular systems, such as the active site of metalloproteins. [29][30][31] We have recently shown that molecular dynamics (MD) simulations, followed by QM/MM calculations, with the QM part described by density functional theory (DFT), provided a detailed structure of the intercalation complexes of dodecanucleotide double-helices with a copper(II) metallointercalator, and formation energy data in good agreement with the experimental DNA-binding constant. 32 On the other hand, detailed local structural information can be experimentally obtained by X-ray crystallography or by NMR spectroscopy only of drug-DNA supramolecular complexes involving small synthetic DNA oligonucleotides, typically in the range 2-12-mer oligonucleotides.…”
Section: Introductionmentioning
confidence: 57%
“…In this context, quantum mechanics/molecular mechanics (QM/MM) calculations provide reliable structural information on a local region of biomolecular systems, such as the active site of metalloproteins. [29][30][31] We have recently shown that molecular dynamics (MD) simulations, followed by QM/MM calculations, with the QM part described by density functional theory (DFT), provided a detailed structure of the intercalation complexes of dodecanucleotide double-helices with a copper(II) metallointercalator, and formation energy data in good agreement with the experimental DNA-binding constant. 32 On the other hand, detailed local structural information can be experimentally obtained by X-ray crystallography or by NMR spectroscopy only of drug-DNA supramolecular complexes involving small synthetic DNA oligonucleotides, typically in the range 2-12-mer oligonucleotides.…”
Section: Introductionmentioning
confidence: 57%